Answer:
The population in 40 years will be 1220.
Step-by-step explanation:
The population of a town grows at a rate proportional to the population present at time t.
This means that:
![P(t) = P(0)e^{rt}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29e%5E%7Brt%7D)
In which P(t) is the population after t years, P(0) is the initial population and r is the growth rate.
The initial population of 500 increases by 25% in 10 years.
This means that ![P(0) = 500, P(10) = 1.25*500 = 625](https://tex.z-dn.net/?f=P%280%29%20%3D%20500%2C%20P%2810%29%20%3D%201.25%2A500%20%3D%20625)
We apply this to the equation and find t.
![P(t) = P(0)e^{rt}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29e%5E%7Brt%7D)
![625 = 500e^{10r}](https://tex.z-dn.net/?f=625%20%3D%20500e%5E%7B10r%7D)
![e^{10r} = \frac{625}{500}](https://tex.z-dn.net/?f=e%5E%7B10r%7D%20%3D%20%5Cfrac%7B625%7D%7B500%7D)
![e^{10r} = 1.25](https://tex.z-dn.net/?f=e%5E%7B10r%7D%20%3D%201.25)
Applying ln to both sides
![\ln{e^{10r}} = \ln{1.25}](https://tex.z-dn.net/?f=%5Cln%7Be%5E%7B10r%7D%7D%20%3D%20%5Cln%7B1.25%7D)
![10r = \ln{1.25}](https://tex.z-dn.net/?f=10r%20%3D%20%5Cln%7B1.25%7D)
![r = \frac{\ln{1.25}}{10}](https://tex.z-dn.net/?f=r%20%3D%20%5Cfrac%7B%5Cln%7B1.25%7D%7D%7B10%7D)
![r = 0.0223](https://tex.z-dn.net/?f=r%20%3D%200.0223)
So
![P(t) = 500e^{0.0223t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20500e%5E%7B0.0223t%7D)
What will be the population in 40 years
This is P(40).
![P(t) = 500e^{0.0223t}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20500e%5E%7B0.0223t%7D)
![P(40) = 500e^{0.0223*40} = 1220](https://tex.z-dn.net/?f=P%2840%29%20%3D%20500e%5E%7B0.0223%2A40%7D%20%3D%201220)
The population in 40 years will be 1220.
Answer:
x= 0.22947
Step-by-step explanation:
Answer:
![t_3(x)=\frac{7\pi}{4}+\frac{7}{2}(x-1)-\frac{7}{4}(x-1)^2+\frac{7}{12}(x-1)^3](https://tex.z-dn.net/?f=t_3%28x%29%3D%5Cfrac%7B7%5Cpi%7D%7B4%7D%2B%5Cfrac%7B7%7D%7B2%7D%28x-1%29-%5Cfrac%7B7%7D%7B4%7D%28x-1%29%5E2%2B%5Cfrac%7B7%7D%7B12%7D%28x-1%29%5E3)
Step-by-step explanation:
We are given that
![f(x)=7tan^{-1}(x)](https://tex.z-dn.net/?f=f%28x%29%3D7tan%5E%7B-1%7D%28x%29)
a=1
![T_n(x)=\sum_{r=0}^{n}\frac{f^r(a)(x-a)^r}{r!}](https://tex.z-dn.net/?f=T_n%28x%29%3D%5Csum_%7Br%3D0%7D%5E%7Bn%7D%5Cfrac%7Bf%5Er%28a%29%28x-a%29%5Er%7D%7Br%21%7D)
Substitute n=3 and a=1
![t_3(x)=f(1)+f'(1)(x-1)+\frac{f''(1)(x-1)^2}{2!}+\frac{f'''(1)(x-1)^3}{3!}](https://tex.z-dn.net/?f=t_3%28x%29%3Df%281%29%2Bf%27%281%29%28x-1%29%2B%5Cfrac%7Bf%27%27%281%29%28x-1%29%5E2%7D%7B2%21%7D%2B%5Cfrac%7Bf%27%27%27%281%29%28x-1%29%5E3%7D%7B3%21%7D)
![f(x)=7tan^{-1}(x)](https://tex.z-dn.net/?f=f%28x%29%3D7tan%5E%7B-1%7D%28x%29)
![f(1)=7tan^{-1}(1)=7\times \frac{\pi}{4}=\frac{7\pi}{4}](https://tex.z-dn.net/?f=f%281%29%3D7tan%5E%7B-1%7D%281%29%3D7%5Ctimes%20%5Cfrac%7B%5Cpi%7D%7B4%7D%3D%5Cfrac%7B7%5Cpi%7D%7B4%7D)
Where ![tan^{-1}(1)=\frac{\pi}{4}](https://tex.z-dn.net/?f=tan%5E%7B-1%7D%281%29%3D%5Cfrac%7B%5Cpi%7D%7B4%7D)
![f'(x)=\frac{7}{1+x^2}](https://tex.z-dn.net/?f=f%27%28x%29%3D%5Cfrac%7B7%7D%7B1%2Bx%5E2%7D)
Using the formula
![\frac{d(tan^{-1}(x))}{dx}=\frac{1}{1+x^2}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%28tan%5E%7B-1%7D%28x%29%29%7D%7Bdx%7D%3D%5Cfrac%7B1%7D%7B1%2Bx%5E2%7D)
![f'(1)=\frac{7}{2}](https://tex.z-dn.net/?f=f%27%281%29%3D%5Cfrac%7B7%7D%7B2%7D)
![f''(x)=\frac{-14x}{(1+x^2)^2}](https://tex.z-dn.net/?f=f%27%27%28x%29%3D%5Cfrac%7B-14x%7D%7B%281%2Bx%5E2%29%5E2%7D)
![f''(1)=-\frac{7}{2}](https://tex.z-dn.net/?f=f%27%27%281%29%3D-%5Cfrac%7B7%7D%7B2%7D)
![f''(x)=-14x(x^2+1)^{-2}](https://tex.z-dn.net/?f=f%27%27%28x%29%3D-14x%28x%5E2%2B1%29%5E%7B-2%7D)
![f'''(x)=-14((x^2+1)^{-2}-4x^2(x^2+1)^{-3}})](https://tex.z-dn.net/?f=f%27%27%27%28x%29%3D-14%28%28x%5E2%2B1%29%5E%7B-2%7D-4x%5E2%28x%5E2%2B1%29%5E%7B-3%7D%7D%29)
By using the formula
![(uv)'=u'v+v'u](https://tex.z-dn.net/?f=%28uv%29%27%3Du%27v%2Bv%27u)
![f'''(x)=-14(\frac{x^2+1-4x^2}{(1+x^2)^3}](https://tex.z-dn.net/?f=f%27%27%27%28x%29%3D-14%28%5Cfrac%7Bx%5E2%2B1-4x%5E2%7D%7B%281%2Bx%5E2%29%5E3%7D)
![f'''(x)=(-14)\frac{-3x^2+1}{(1+x^2)^3}](https://tex.z-dn.net/?f=f%27%27%27%28x%29%3D%28-14%29%5Cfrac%7B-3x%5E2%2B1%7D%7B%281%2Bx%5E2%29%5E3%7D)
![f'''(1)=-14(\frac{-3(1)+1}{2^3})=\frac{7}{2}](https://tex.z-dn.net/?f=f%27%27%27%281%29%3D-14%28%5Cfrac%7B-3%281%29%2B1%7D%7B2%5E3%7D%29%3D%5Cfrac%7B7%7D%7B2%7D)
Substitute the values
![t_3(x)=\frac{7\pi}{4}+\frac{7}{2}(x-1)-\frac{7}{4}(x-1)^2+\frac{7}{2\times 3\times 2\times 1}(x-1)^3](https://tex.z-dn.net/?f=t_3%28x%29%3D%5Cfrac%7B7%5Cpi%7D%7B4%7D%2B%5Cfrac%7B7%7D%7B2%7D%28x-1%29-%5Cfrac%7B7%7D%7B4%7D%28x-1%29%5E2%2B%5Cfrac%7B7%7D%7B2%5Ctimes%203%5Ctimes%202%5Ctimes%201%7D%28x-1%29%5E3)
![t_3(x)=\frac{7\pi}{4}+\frac{7}{2}(x-1)-\frac{7}{4}(x-1)^2+\frac{7}{12}(x-1)^3](https://tex.z-dn.net/?f=t_3%28x%29%3D%5Cfrac%7B7%5Cpi%7D%7B4%7D%2B%5Cfrac%7B7%7D%7B2%7D%28x-1%29-%5Cfrac%7B7%7D%7B4%7D%28x-1%29%5E2%2B%5Cfrac%7B7%7D%7B12%7D%28x-1%29%5E3)
(x - 2) is a factor of the polynomial
Give me feedback
Answer: 10 I think not sure
Step-by-step explanation: 1/2 base times height-> 1/2(6•10)